A cartilha como instrumento para auxiliar o desenvolvimento de projetos de educação ambiental - Klein, Carine Leal (2018)
Over the years, man, through the inappropriate use of natural resources, has been attacking the environment and causing him irreparable damage. Advances in science and technology have contributed to this. In order to minimize such consequences, avoiding a collapse, there are mechanisms of environmental governance, such as The United Nations Environment Program; the Commission for Sustainable Development and national and international nongovernmental organizations seeking agreements and alternatives to minimize such problems. But it is also necessary for man to become aware of the need to change habits and attitudes. Within the scope of education, from 1997, the environment becomes a cross-cutting theme in the basic curricula of Elementary Education, according to the new curriculum proposal of the Ministry of Education, called National Curricular Parameters-NCP. The present work is linked to the research line: Theoretical Foundations for Teaching Science and Mathematics and sought to develop an Educational Product (EP) with the intention of contributing to Environmental Education (EE) in Science Teaching. For this, an Environmental Primer was developed, which will serve as a pedagogical tool to assist in the development of Environmental Projects in science classes, which accompanies the present dissertation and is entitled “Environmental Education - your attitudes make a difference!”. The EP was applied in a class of the 5th year of elementary school in a municipal school in Palmeira das Missões - RS. The data for elaboration and development of the research were obtained through a semistructured questionnaire applied to the students and by the Logbook used by the researcher teacher. The results obtained showed that the realization of environmental projects is an indicated practice to make scien ce teaching more attractive, causing students to increase their knowledge and create conditions to improve the environmental situation of their communities. Also, the use of pre -established content and activities can facilitate the execution of activities by teachers and thus make EE more present and more meaningful in the daily lives of all citizens. This dissertation accompanies the educational product, which is available at http://educapes.capes.gov.br/handle/capes/429324.